Eating habits and physical activity of Saudi women before and during the COVID-19 pandemic - Hanan Badr; Orjwan Alsiari; Rahaf Alshehri; Arwa Althobate; Dalia Bahasan; Faygah Shibily; Rasha Alsaigh; Salmah Alghamdi (Belitung Raya Foundation, 2022)
Background: During the COVID-19 pandemic, the lives of many people have been affected, and their lifestyles changed, including their eating habits and levels of physical activity. Objective: This study aimed to assess lifestyle changes among Saudi women before and during the COVID-19 pandemic. Methods: The study used a cross-sectional descriptive design. Participants were recruited via social media (WhatsApp, Twitter, and Facebook), and the data were collected in March 2021 through Godin-Shephard Leisure-Time Physical Activity questionnaire and eating habits questionnaire. Chi-square and t-tests were used for data analysis. Results: The number of participants included in the analysis was 979. The results of the study showed no statistically significant difference in the BMI (t = 1.29, p = 0.15) or physical activity (t = 1.49, p = 0.135) when comparing the time before and during the pandemic. However, there were changes in their eating habits, including changes in the relative frequency of eating home-cooked meals and ordering from restaurants. Ordering restaurant meals per week decreased from 78.2% before COVID-19 to 47.5% during the pandemic. Moreover, there was a marked increase in anxiety reported about food hygiene from outside sources, from 14.7% before COVID-19 to 63% during the pandemic. Regarding physical activity, 41.7% said the pandemic had moderately affected their physical activity. The home was the most common setting for exercise both before and during the pandemic, but the percentage of participants exercising exclusively at home was almost doubled during the pandemic, from 46% before the pandemic to 81% during the pandemic. Conclusion: Dietary habits have changed in a good way during the pandemic; participants increased their consumption of home-cooked meals rather than eating restaurant meals.  Also, the participants were more anxious about food hygiene during the COVID-19 pandemic.